Experimental and numerical analysis of impact on curved nanocomposite panels. Issue 16 (18th August 2019) - Bidi, Ahmad; Liaghat, Gholamhossein; Rahimi, Gholamhossein; Hadavinia, Homayoun
ABSTRACT: In this work nanopolyurea is used as reinforcement for curved steel plates under low velocity impact loading. Experimental and numerical analysis are used to study the effect of plate curvature and nano particle effects. A drop weight test apparatus is utilized to apply impact loading on bi-layer panels. Experiments show that maximum improvement in energy absorption capacity of nanopolyurea is about 5%. Numerical analysis is carried out using explicit LS-DYNA solver. The results show that by increasing panel radius of curvature, impact force increases; also comparison between numerical and experimental results shows a good agreement.